CYTOKININ AND FLASK SEALING AFFECT SHOOT PROLIFERATION AND In Vitro DEVELOPMENT OF Jacaranda cuspidifolia MART. MICROCUTTINGS - Ferreira,Deise Kelle Barbosa (2022)
ABSTRACT Plant growth regulators (PGRs) and types of flasks sealing that allow gas exchange can favor the development of in vitro plant propagation systems. The objective of the present study was to evaluate the eff ects of cytokinin supplementation on the induction of shoot proliferation and the influence of gas exchange on the in vitro development of Jacaranda cuspidifolia Mart microcuttings. Nodal segments were cultured in medium supplemented with diff erent concentrations (0.25; 0.5; 1.0 and 2.0 mg L-1) of 6-benzyladenine (BA). In the control treatment, there was no addition of PGRs. After 30 days of culture, the microcuttings were isolated and transferred to a rooting medium supplemented with 1.0 mg L-1 indole-3-butyric acid. At this stage, the culture fl asks were sealed with rigid polypropylene lids with a porous membrane (1 M; 21 μL L-1 s-1 CO2) or with no membrane (0 M; 14 μL L-1 s-1 CO2). Cytokinin supplementation induced the activation of axillary buds of J. cuspidifolia. The highest numbers of shoots were observed in explants cultivated in the presence of 0.5–1.0 mg L-1 BA. The microcuttings kept in flasks with a higher level of gas exchange (1M) had a higher percentage of rooting and greater root and shoot lengths. Microscopic analysis showed a greater differentiation of leaf tissues in plants kept in flasks with a higher level of gas exchange (1M). These plants also showed greater mesophyll thickness and, consequently, greater leaf blade thickness. The results provide new information for establishing an efficient in vitro propagation system for J. cuspidifolia.